Ideologi Merdeka Belajar dalam Pembelajaran Musik: Analisis Kompetensi Pedagogik, Adaptasi Profesional, dan Otonomi Guru Seni Budaya - Salafiyah, Nafik; Malarsih; Sucipto Hadi Purnomo (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the ideology of Freedom of Learning in music learning through the integration of pedagogic competence, professional adaptation, and autonomy of cultural arts teachers as a framework for the development of contextual learning practices. The research method uses a descriptive qualitative approach through literature study and conceptual analysis of educational policies, pedagogic theories, and contemporary music learning practices. Data analysis was carried out thematically to identify the relationship between educational ideology, teacher professionalism, and music learning dynamics. The results of the study show that the ideology of Merdeka Belajar strengthens the role of teachers as reflective agents who have the freedom to design creative learning strategies based on local culture and the needs of students. The integration of pedagogic competencies and adaptive professionalism enhances learning flexibility, student active participation, and meaningful, student-centered musical experiences. This study concludes that the ideology of Independent Learning functions as a pedagogic paradigm that supports the development of innovative, contextual, and transformative music learning models in contemporary cultural arts education strategies based on local culture and the needs of students. The integration of pedagogic competencies and adaptive professionalism enhances learning flexibility, student active participation, and meaningful, student-centered musical experiences. This study concludes that the ideology of Freedom of Learning functions as a pedagogic paradigm that supports the development of innovative, contextual, and transformative music learning models in contemporary cultural arts education Keywords: Arts And Culture Curriculum, Critical Pedagogy, Merdeka Belajar, Music Education, Professional Adaptation, Teacher Autonomy.